Sandwich and Laminated Composite Structures Under Ballistic, Blast and Combined Loading : A Systematic Literature Review - Muhammad Abdul Ghofur; Leonardo Gunawan; Satrio Wicaksono; Ditho Ardiansyah Pulungan (Institut Teknologi Dirgantara Adisutjipto, 2026)
Lightweight protective structures are increasingly required to resist ballistic penetration, blast impulse, and sequential combined threats. However, evidence on laminated and sandwich composites remains fragmented across threat types, architectures, and testing protocols. This systematic literature review followed Preferred Reporting Items for Systematic Reviews and Meta Analysis (PRISMA) framework, searched Scopus for peer-reviewed journal articles published from 2016 to 2025, and retained 36 eligible quantitative studies from 57 records. The synthesis links structural architecture, dominant failure mechanism and performance metrics across laminates and sandwich systems. Evidence indicates that laminated composites generally provide superior ballistic penetration resistance, whereas sandwich composites offer greater blast mitigation. Hybrid skined sandwich architectures emerge as a promising strategy for combined loading, although standardized validation remains limited. The review contributes an architecture-mechanism-metric framework. Overall, deployable protective systems should be selected by threat specific requirements rather than broad architectural superiority claims.